INTER-OBSERVER VARIABILITY IN GLEASON SCORING SYSTEM F0R HISTOLOGICAL GRADING OF ADENOCARCINOMA PROSTATE - Ahsan, Farah; Khan, Ahmed Ahson; Asif, Muhammad; Aslam, Maria; Hamayun, Saba; Din, Hafeez Ud (Pakistan Armed Forces Medical Journal, 2022)
ABSTRACTObjective: To evaluate the reproducibility of the Gleason scoring system and to compare its inter-observer variability for histological grading of prostatic adenocarcinoma.Study Design: Prospective double-blind study.Place and Duration of Study: Histopathology department of Armed Forces Institute of Pathology (Jan-Jul 2020).Methodology: A total of 128 pathology slides of prostate biopsies from patients with prostate cancer were re-evaluated. The International Society of Urological Pathology 2005 modified Gleason grading system with Epstein’s modification was used. Two pathologists, blinded to each other and to the initial pathology report, performed the pathological evaluation. To determine inter-observer concordance, the kappa coefficient test was used.Results: Concordance rates between the two observers for Gleason pattern sums were 67% (Ꝁ=0.556, 95% CI 0.40-0.59), respectively. Best concordance was at Gleason sum 7 (n=30/128).Conclusion: The agreement between observers on the Gleason sum was moderate. It can be greatly reduced if better trained uropathologists employ the Gleason scoring system resulting in less variability and more conformity.